Election meltdown : dirty tricks, distrust, and the threat to American democracy - Hasen, Richard L. (New Haven : Yale University Press, 2020)
From the nation's leading expert, an indispensable analysis of key threats to the integrity of the 2020 American presidential election.
The new voting wars -- The icicle -- The weakest link -- Dirty tricks -- "Stolen" -- Surviving 2020 and beyond.
Includes bibliographical references and index.
Online resource; title from digital title page (EBSCOhost, viewed March 3, 2021).
JSTOR
Keywords: Elections -- United States; Voting -- United States; Voter suppression -- United States; Elections -- Corrupt practices -- United States; United States -- Politics and government -- 2017-2021.; Democracy -- United States; Vote -- États-Unis.; Corruption électorale -- États-Unis.; États-Unis -- Politique et gouvernement -- 2017-2021.; POLITICAL SCIENCE -- Political Process -- Elections; Democracy; Elections; Elections -- Corrupt practices; Politics and government; Voter suppression; Voting; United States; 2017-2021; Electronic book